Efficiency of Universities and Research-Focused Institutions Worldwide: An Empirical DEA Investigation Based on Institutional Publication Numbers and Estimated Academic Staff Numbers - Lutz Bornmann; Sabine Gralka; Félix de Moya Anegón; Klaus Wohlrabe (Center for Economic Studies and ifo Institute (CESifo), 2020)
One of the core indicators in the field of scientometrics is the number of papers published by a unit within a given period. However, such indicators can only be assessed properly by considering the unit's available resources. When evaluating the efficiency of institutions worldwide, the problem concerning the availability of internationally standardized data arises. While on the output side consistent publication indicators are available, these data are frequently not available on the input side. We therefore introduce a new input indicator based on the authors' mentions in the institutions' papers. We calculate efficiency scores for more than 4,800 universities and other research-focused institutions worldwide. "Harvard University" is the best performing institution (in all years) followed by many other institutions from Northern America or Europe. The results of the study show that institutions in the Pacific region have the highest average efficiency scores, followed by Northern America and Western Europe. While many results of this study are scarcely surprising, it is the first time that an efficiency analysis is being performed for a multitude of institutions worldwide using a standardized input indicator. It seems that the new proxy indicator based on co-authors is suitable for reflecting institutional staff numbers.
Keywords: I21; I23; D61; H52; 330; bibliometrics; efficiency; data envelopment analysis; universities; research-focused institutions; world